Socialization of Aisyiyah Women's Participation - Adawiyah, Sa'diyah El; Endang Sulastri (Salus Publica: Journal of Community Service, 2024)
Political participation is the activity of a person or a group of people to actively participate in political life by electing state leaders directly or indirectly, in influencing government policies. Community service activities carried out by the Jakarta PWA Law and Human Rights Council in the Socialization Activity to Increase Women's Participation in the 2024 Jakarta Regional Elections with the following objectives: Increasing the understanding and knowledge of 'Aisyiyah women in political participation in the 2024 regional elections, especially their rights and votes. The activity is in the form of socialization of women's participation in the 2024 regional elections. The participants who attended were representatives of the DKI Jakarta PWA Assembly and institutions, members of the DKI Jakarta PWA Law and Human Rights Assembly, PDA throughout DKI Jakarta, the chairman of the regional leadership of NA, IPM, IMM and IGASI and IGABA, which in total met 150 participants. The results of this community service activity have added new and refreshing insights for 'Aisyiyah women. Increasing knowledge and changing attitudes about the regional elections and the role of 'Aisyiyah women in making them aware of the role of women in fighting for better women's rights through general elections by electing candidates for governor and deputy governor who understand women's rights